Semi-analytic galaxies. III: the impact of supernova feedback on the mass-metallicity relation - Collacchioni, Florencia (2018)
We use the semi-analytic model (SAM) of galaxy formation and evolution SAG coupled with the MULTIDARK simulation MDPL2 to study the evolution of the stellar - gas metallicity relation of galaxies (MZR). We test several implementations of the dependence of the mass loading due to supernovae (SNe).We find that no evolution in the normalization of the MZR is obtained unless we introduce an explicit scaling of the reheated and ejected mass with redshift as (1 + z)β. The latter is in agreement with results from the FIRE simulations, and it should encompass small-scale properties of the interstellar medium varying over time, which are not captured in SAMs, as well as other energy sources in addition to SNe. Increasing β leads to stronger evolution of the MZR normalization; β = 1.9 reproduces the observed MZR in the range 0 < z < 3.5. A stronger redshift dependence of outflows reduces the levels of star formation at earlier epochs with the consequent decrease of metal production. This leads to a slower increase of the gas metallicity compared to the stellar mass build-up. The cold gas can be contaminated either by receiving a direct injection of the material recycled by stellar winds and SNe or by gas cooling. The relative role of each process for a given stellar mass depends on the criterion adopted to regulate the fate of the recycled material. However, modifying the metal loading of the outflows has mild impact on the zero-point evolution and does not affect our conclusions.